The Research on Driving Meta-model of Large Rotary-type Cylindrical Antenna. Issue 1 (July 2021) - Zhiping, Chen; Yongwei, Wan; Xi, Ling; Yu, Chen; Chunguang, LI
Abstract: As a complex system with highly integrated multi-discipline, the large rotary-type cylindrical antenna is favored by more and more researchers in IPS detection and large-area survey observation. Due to its complex structure, huge volume and large motion inertia, high requirements on the drive system are indispensable, and there exist some certain limitations in the traditional system design method. This article proposes a large rotary-type cylindrical antenna driving system modeling method based on the meta-model. The domain-specific modeling language of the antenna driving system is defined by extending SysML, and the domain meta-model of the antenna driving system is constructed on this basis. The functional modeling of the antenna driving system is based on the meta-model to support the analysis of the antenna driving process, improve the modeling efficiency and model reusability, and provide a research foundation for the subsequent system modeling design of large antenna.